(untitled) (Research, Society and Development, 2019)
The aim of this paper was to evaluate the Physical Education students’ contents and performance about Inclusive Education on the National Exam of Student Performance (Enade/Inep). For this, the study is divided into two stages: an integrative review, which grounds the context about Physical Education teachers’ formation and performance on Inclusive Education of disabled people and psychometric analysis of the questions about Inclusive Education on Enade (2004 to 2017). In the integrative review, the absence of specific training, lack of multidisciplinary work and needs of new resources could be identified. In the psychometric analysis, most of the items indicating medium and difficult rates, discrimination rates good or very good, also the level applying or higher in Bloom’s Taxonomy Revised were also observed. Higher performance was observed among students who were female, studied in public HEI and also were from the Northeast and North regions. Understanding the Enade as an important mechanism in verifying the performance in initial formation, it is necessary a better involvement between HEIs and students with the knowledge which grounds this theme in the academic context and in social intervention, since the exam is well organized and its literature indicates the importance of this training.